A novel mutation in the SLC5A2 gene causing benign renal glucosuria - Sofia Vasconcelos; Francisca Freitas; Alícia Rebelo; Andreia Lopes; Bárbara Pereira (Hygeia Press di Corridori Marinella, 2021)
Glucosuria is defined as a detectable amount of glucose levels in urine. It can be isolated or associated with other pathologies. In the presence of glucosuria in children and adolescents, it is important to perform an etiological study to exclude these conditions. Isolated renal glucosuria is a rare tubular disorder characterized by glucosuria without hyperglycemia or other glucose metabolism disorders. The inherited form of this disorder is called Familiar Renal Glucosuria (FRG). This is a rare condition caused by mutations in the SLC5A2 gene (that encodes SGLT-2), which are responsible for the majority of cases. The long-term outcome of patients with FRG is very good, with no recorded mortality. The authors report a case of a 6-year-old girl with glucosuria that was found incidentally, without any symptoms or abnormalities in physical examination. Laboratory tests and urinalysis were normal, despite the presence of glucose in urine. The genetic test showed homozygotic missense mutation in the SLC5A2 gene. With this case report, the authors would like to alert to this entity and to highlight the importance of pediatric renal glucosuria management and differential diagnosis.